Recent insights into the electrochemical behavior of blended lithium insertion cathodes: A review. (10th April 2018) - Heubner, C.; Liebmann, T.; Schneider, M.; Michaelis, A.
Abstract: The blending of different lithium insertion compounds has been proven to be a promising approach to design advanced electrodes for future lithium-ion batteries. Blending of certain lithium insertion compounds is done to combine the best properties of the individual active materials and to improve the energy or power density as well as cycling and storage durability. Furthermore, the blend can be tailored to meet specific requirements regarding costs, environmental issues and safety aspects. Herein, we report recent insights into the electrochemical behavior of blended lithium insertion cathodes. This review does not claim to summarize all recent literature, but rather is a critical overview of blended lithium insertion cathodes based on recent research findings. Latest thermodynamic studies enlighten certain mechanisms particularly occurring in blended insertion electrodes. Recent reports on active material combinations, including type-, mass ratio- and design-dependencies, reveal substantial improvements and synergetic effects regarding the electrochemical properties of the blended electrodes. Special experimental methods and setups are developed and applied to examine transport processes in blended insertion electrodes, revealing significant differences towards insertion electrodes containing a single type of active material. First approaches of modeling and simulation of blended insertion electrodes provide valuable information on the microscopic processes within the electrode and adequately reflect the experimental findings on the macro scale.